Verfeindete Brüder
The report focuses on a newly independent Slovenia and its attempts to join Europe. The report particularly analyzes the numerous political parties. The question of the 60,000 refugees is addressed, as well as the fishing rights and Kopar harbor dispute between Slovenia and Croatia. Interviewed are the new leaders of Slovene public life. Bozo Kovac, chief editor of the daily Republika, talks about freedom of the press and occasional political pressure. He further states that Slovenia must privatize herself in order to attract foreign capital. Rade Serbedzija, a Serb actor born in Croatia, choose Slovenia as his new home. He talks about being politically haunted in Serbia and Croatia to the point of his life being threatened. He explains that Slovenia successfully escaped from the Balkan hell. Zmago Jelincic, leader of the Slovenian National Party, discusses the need for Slovenia to be ethnically clean. He compares Slovenia to Austria, which as he states had had a policy of extricating foreigners. Wife of Momir Kandic, a Slovene, talks about her husband who was forced to leave Slovenia for four years because he refused to give up his Serbian citizenship. Milan Kucan, President of Slovenia, reflects on the Kandic case, stating that the law required everyone in the JNA [Yugoslav army] to leave their positions and renounce their Serbian citizenship in order to remain Slovenian citizens. Kucan gives an optimistic account about Slovenia's future. He sees the need for Slovenia's political parties to work together on taking care of solvable problems in the economy and society. He states that companies have to restructure themselves if they want to participate in the world market. Raimund Zlatko Fers, the leader of the Steirische Christian Democrats, talks about the desire of that province to separate economically from Slovenia. Remaining footages show Slovenia dailies and a the Republika publishing agency, refugees in Slovenia, meeting between Franjo Tudjman (Croatia's president) and Milan Kucan (Slovenia's president), people gathering in the street around the Slovenian National Party booth, Momir Kandic family, and commercials for the Liberal Democratic Party and the Slovenian National Party.